STUDY OF THE HUMAN PAPILLOMA VIRUS PREVALENCE AND ITS PHYSICAL STATUS IN PATIENS WITH NON-SMALL CELL LUNG CANCER - M. K. Ibragimova; M. M. Tsyganov; A. M. Pevzner; E. O. Rodionov; O. V. Cheremisina; S. V. Miller; S. A. Tuzikov; N. V. Litviakov (Сибирский онкологический журнал)
To date, the role of human papillomavirus (HpV) in the development of lung cancer is still under investigation. The available published data do not provide evidence of the involvement of HpV in lung cancer pathogenesis. In Russia, there are no reports regarding the studies of viral contribution to lung carcinogenesis.The aim of the present study was to examine the presence of high-risk HpV infection in patients with non-small cell lung cancer (NSCLC).Material and Methods. The study included 30 patients with histologically verified stage IIBIIIA NSCLC. Normal and tumor lung tissue samples as well as whole blood samples from each patient were used. dNA was isolated from tissue samples using the QIAamp dNA mini Kit (Qiagen, Germany). Amplisens® reagent kits (Moscow, Russia) were used for dNA isolation and genotyping.Results. The presence of HpV dNA was detected in 3 (10.0 %) patients. HpV dNA was not detected in 27 (90.0 %) patients. HpV-16 genotype was observed in 2 HpV-positive patients, and HpV-33 was observed in 1 patient. A clinically insignificant viral load was found in almost all HpV-positive samples. The assessment of the virus integration in HpV16-positive lung cancer patients revealed mixed and integrated forms of the virus in the tumor tissue of these patients. The 5-year metastasis-free survival rate in all HpV-positive patients was 100 %.Conclusion. Our data showed HpV dNA prevalence rate of 10 % among NSCLC patients in the Russian population. The presence/absence of a viral component for lung cancer patients is a clinically significant parameter.